1987
DOI: 10.1086/165494
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution images of the L1551 bipolar outflow - Evidence for an expanding, accelerated shell

Abstract: Approximately one-half of the L1551 bipolar outflow was mapped in the J = 1-0 transition of 12CO using the FCRAO 14 m telescope. The data were obtained by heavily oversampling over the beam area and then were reconstructed using a maximum entropy algorithm to obtain images of the high-velocity gas with an angular resolution of approximately 20". The outflow exhibits a striking shell-like structure with the lowest velocity out-flowing gas found along the limb of the outflow, and the highest velocity outflowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…While the shell of relatively slow gas in the L1448 outflow is similar to what is seen in more evolved outflows like L1551 (e.g., Moriarty-Schieven et al 1987), and therefore likely composed of accelerated ambient gas, the nature of the EHV component is still mysterious. The symmetry, high speed, and fragmented appearance of the EHV gas initially suggested that it may consist of a collection of molecular "bullets" ejected by the central protostar and traveling along the outflow axis (Bachiller et al 1990).…”
Section: Introductionmentioning
confidence: 87%
“…While the shell of relatively slow gas in the L1448 outflow is similar to what is seen in more evolved outflows like L1551 (e.g., Moriarty-Schieven et al 1987), and therefore likely composed of accelerated ambient gas, the nature of the EHV component is still mysterious. The symmetry, high speed, and fragmented appearance of the EHV gas initially suggested that it may consist of a collection of molecular "bullets" ejected by the central protostar and traveling along the outflow axis (Bachiller et al 1990).…”
Section: Introductionmentioning
confidence: 87%
“…The evolutionary algorithm, used here, is described in Promislov (1999). We estimated the effective HPBW of the reconstruction in a manner, similar to that used by Moriarty-Schieven et al (1987). For each point of a map we subtracted the contribution from the source leaving us with the noise fluctuations only.…”
Section: Observationsmentioning
confidence: 99%
“…Bachiller 1996). Part of this difficulty is due to the large variety of shapes and velocity patterns observed in the outflow-accelerated gas, which range from the almost parabolic shells of low velocity material detected in L1551 and Mon R2 (Moriarty-Schieven et al 1987;Meyers-Rice & Lada 1991) to the collimated jets of rapidly moving gas observed towards L1448-mm and HH211 (Bachiller et al 1990;Gueth & Guilloteau 1999). In addition to the molecular gas, optical observations of outflows often reveal an atomic component of higher excitation and collimation, probably due to recently shocked material either in the wind itself or at the interface between the wind and the cloud.…”
Section: Introductionmentioning
confidence: 99%